The Dynamics of Women's Political Participation and an Evaluation of Gender Representation in the Provincial Parliament of Gorontalo - Andi Yusuf Katili; Ratih Arifin; Agus Pariono (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze the dynamics of women’s political participation and evaluate gender representation in the Provincial Parliament of Gorontalo. Using a qualitative approach, data were collected through in-depth interviews with female politicians, election organizers, and voters from various community groups, complemented by documentation and observation. The findings reveal that women’s representation in the Gorontalo parliament has increased quantitatively, largely due to affirmative policies such as the 30% quota. However, this representation does not yet fully reflect substantive involvement in legislation and decision-making processes. Structural barriers, including political party dominance and high political costs, alongside cultural obstacles such as patriarchal norms and the double burden faced by women, remain significant challenges. Nevertheless, a positive trend emerges among young voters and parts of society who consider women’s participation essential for producing more inclusive policies. These findings highlight the need for synergy between internal party reforms, capacity-building for women, and civic political education to ensure that women’s representation is not merely symbolic but also meaningful. Thus, this research contributes to a deeper understanding of women’s political representation at the regional level and offers strategic recommendations for fostering a more inclusive and gender-equitable democracy.